Evaluasi Tehnik Relaksasi Yang Paling Efektif Dalam Penatalaksanaan Nyeri Persalinan Kala I Terhadap Keberhasilan Persalinan Normal - Herawati, Rika (Jurnal Martenity and Neonatal, 2016)
The pain and pain during labor and delivery is basically due to the strong contractions during labor and it is a natural thing. Every woman has pain that is different. The pain can occur due to physical factors or other physiological or may also arise due to emotions or feelings on the woman. This is because the negative suggestion factors that enter into the subconscious mind, which is where the subconscious mind can not distinguish between reality and imagination. Tension and fear felt by the mother causes pain during labor, thus slowing the delivery process. Of the many relaxation techniques to reduce pain during childbirth whom will muscle relaxation techniques, breathing, thinking and visual. The purpose of this study was to evaluate the most effective relaxation techniques in pain management to the success of the first stage of labor Normal labor in Private Practice Midwife Syaflina Fitri Rokan Hulu. Types of Research at theÂ Experimental design One group pretest and post test, with a total population of all women who give birth in BPS Saflina Fitr during the 2 months of May and June 2015. The total sampling method. Data analysis was performed using univariate, bivariate correlation test Product Moment. From the results of research it was found that breathing relaxation techniques are most effective in reducing labor pain of the first stage which is 40% of the total number of respondents 20 people. It is suggested to midwife that teach pregnant women breathing technique thus only in the third trimester ANC.